Impact of Psychological and Social Climacteric Changes upon Quality of Life of Middle Age Women in Baghdad City - Muhson, wafaa; Amir, fatin (Iraqi National Journal of Nursing Specialties, 2015)
Objective: to assessthe impact of psychological and social climacteric changes on quality of life amongmiddle age women in Baghdad cityMethodology: : A descriptive analytic study was conducted to study the quality of life among middle agewomen due topsychological and social climacteric changes from February 2013- July 2013. A purposivesampleconsisted of three hundred (300) womenaged (40-65) years who were attending health centers in twosectors in Baghdad / AL- Russafa andAL- karhk . The data were collected through using interview technique ,and questionnaire format , which comprises two parts, first part consist (socio-demographic characteristic , thesecond part quality of life domains (psychological and social domains ) .. The reliability of the questionnairewas determined through a pilot study and, the validity through a panel of (18) experts. Descriptive and inferentialstatistical analysis procedures were employed for data analysis; all the statistical procedures were tested at P>0.05 or less .Results:The results show that the climacteric changes for ( psychological domain ) was reported by morethan half of study sample which assessed as ( moderate) impact on quality of life .while the assess of socialdomain ( good).Recommendation:The study recommends for more effort from health care providers to do further researchesabout the quality of life of middle age women. Moreover, the health care provider should implement aneducational program for women about the climacteric changes and how to pass it safely